Outside the bubble : social media and political participation in western democracies - Vaccari, Cristian; Valeriani, Augusto (New York, NY : Oxford University Press, 2021)
"The ways in which citizens experience politics on social media have overall positive implications for political participation and equality in Western democracies. This book investigates the relationship between political experiences on social media and institutional political participation based on custom-built post-election surveys on samples representative of internet users in Denmark, France, Germany, Greece, Italy, Poland, Spain, the United Kingdom, and the United States between 2015-18. On the whole, social media do not constitute echo chambers, as most users see a mixture of political content they agree and disagree with. Social media also facilitate accidental encounters with news and exposure to electoral mobilization among substantial numbers of users. Furthermore, political experiences on social media have relevant implications for participation. Seeing political messages that reinforce one's viewpoints, accidentally encountering political news, and being targeted by electoral mobilization on social media are all positively associated with participation. Importantly, these political experiences enhance participation especially among citizens who are less politically involved. Conversely, the participatory benefits of social media do not vary based on users' ideological preferences and on whether they voted for populist parties. Finally, political institutions matter, as some political experiences on social media are more strongly associated with participation in majoritarian systems and in party-centric systems. While social media may be part of many societal problems, they can contribute to the solution to at least two important democratic ills-citizens' disconnection from politics and inequalities between those who choose to exercise their voice and those who remain silent"--
Includes bibliographical references and index.
Keywords: Political participation -- Technological innovations -- Europe; Political participation -- Technological innovations -- United States